Emotional reactions of medical doctors and students following the loss of their patients at the Dr George Mukhari Hospital emergency unit, South Africa - Tsego Masia; W.J. Basson; Gboyega A. Ogunbanjo (South African Family Practice)
Background: Studies on death and dying predominantly emphasise the needs of the dying patient and the process of bereavement. Few studies have focused on the reactions of medical doctors and students when the patients they have cared for die.